Evaluating an impact origin for Mercury's high‐magnesium region. Issue 3 (25th March 2017) - Frank, Elizabeth A.; Potter, Ross W. K.; Abramov, Oleg; James, Peter B.; Klima, Rachel L.; Mojzsis, Stephen J.; Nittler, Larry R.
Abstract: During its four years in orbit around Mercury, the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) spacecraft's X‐ray Spectrometer revealed a large geochemical terrane in the northern hemisphere that hosts the highest Mg/Si, S/Si, Ca/Si, and Fe/Si and lowest Al/Si ratios on the planet. Correlations with low topography, thin crust, and a sharp northern topographic boundary led to the proposal that this high‐Mg region is the remnant of an ancient, highly degraded impact basin. Here we use a numerical modeling approach to explore the feasibility of this hypothesis and evaluate the results against multiple mission‐wide data sets and resulting maps from MESSENGER. We find that an 3000 km diameter impact basin easily exhumes Mg‐rich mantle material but that the amount of subsequent modification required to hide basin structure is incompatible with the strength of the geochemical anomaly, which is also present in maps of Gamma Ray and Neutron Spectrometer data. Consequently, the high‐Mg region is more likely to be the product of high‐temperature volcanism sourced from a chemically heterogeneous mantle than the remains of a large impact event. Plain Language Summary: During its four years in orbit around Mercury, chemical measurements from the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) spacecraft revealed a large region of unusual composition relative to the rest of the planet. Its elevated magnesium abundance, in particular, led to the name of the "high‐magnesium region" (HMR). High magnesium abundance in rock can be an indicator of its origin, such as high‐temperature volcanism. Although the HMR covers approximately 15% of Mercury's surface, its origin is not obvious. It does roughly correspond to a depression with thin crust, which previously led to the hypothesis that it is an ancient impact crater that was large enough to excavate mantle material, which, in rocky planets, is rich in magnesium relative to their crust. Here we use a model to simulate how such a crater would look and compare the results to data collected by MESSENGER. We find that the processes required to erase clear physical signs of an HMR‐scale crater should also have erased the strong chemical signature of the HMR. Thus, we conclude that the HMR is more likely due to high‐temperature volcanism than a mantle‐excavating impact. Key Points: We model the putative high‐Mg region impact on Mercury and evaluate MESSENGER data for lingering signs of the basin It is difficult to degrade a large basin on Mercury while preserving its strong geochemical signature The high‐Mg region is most likely the result of high‐temperature volcanism and mantle heterogeneities